2018
DOI: 10.3389/fneur.2018.00965
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hemorrhage Induces Cardiac Dysfunction in Mice Without Primary Cardiac Disease

Abstract: Background: Intracerebral hemorrhage (ICH) is a life threatening stroke subtype and a worldwide health problem. In this study, we investigate brain-heart interaction after ICH in mice and test whether ICH induces cardiac dysfunction in the absence of primary cardiac disease. We also investigate underlying mechanisms such as oxidative stress and inflammatory responses in mediating cardiac dysfunction post-ICH in mice.Methods: Male, adult (3–4 m) C57BL/6J mice were subjected to sham surgery or ICH using an autol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…Cardiac complications are common after ICH and higher heart rate variability in the acute phase is associated with poorer 3-month outcomes. 62 Preclinical studies using autologous blood or collagenase-induced ICH in mice have replicated cardiac complications 59,63 and metoprolol reduced cardiac damage by abrogating sympathetic overactivation in addition to its immunosuppressive effects. 59 Furthermore, splenectomy reduced cardiac dysfunction along with improving neurological outcome after autologous blood-induced ICH in mice.…”
Section: Ich Sequelae and Improving Recoverymentioning
confidence: 99%
“…Cardiac complications are common after ICH and higher heart rate variability in the acute phase is associated with poorer 3-month outcomes. 62 Preclinical studies using autologous blood or collagenase-induced ICH in mice have replicated cardiac complications 59,63 and metoprolol reduced cardiac damage by abrogating sympathetic overactivation in addition to its immunosuppressive effects. 59 Furthermore, splenectomy reduced cardiac dysfunction along with improving neurological outcome after autologous blood-induced ICH in mice.…”
Section: Ich Sequelae and Improving Recoverymentioning
confidence: 99%
“…Intracerebral hemorrhages are the most common stroke subtype, accounting for 10%-15% of all strokes, with an estimated annual global incidence of 16 per 100,000 people [44][45][46]. About 4% of patients with an intracerebral hemorrhage experience a series of cardiac complications, such as acute myocardial infarction, ventricular fibrillation, acute heart failure, and cardiac death within two days, of which acute heart failure is the most common serious in-hospital cardiac event [47,48]. SAHs are mainly caused by ruptured aneurysms, with a worldwide incidence of approximately nine per 100,000 people and a mortality rate of about 60% at six months [49,50].…”
Section: Cardiac Damage Induced By a Brain Hemorrhagementioning
confidence: 99%
“…A retrospective study of 617 consecutive patients with SAH also showed increased mortality in patients with high cTnI levels [53]. Therefore, serum cTn levels can be used as indicators to predict hospital mortality and poor prognosis and are available for risk stratification during intracerebral hemorrhage hospitalization [47].…”
Section: Cardiac Damage Induced By a Brain Hemorrhagementioning
confidence: 99%
“…Neurogenic heart dysfunction has been recorded in multiple acute neurological conditions, such as subarachnoid haemorrhage (SAH) intracerebral haemorrhage, traumatic brain injury (TBI) and acute ischemic stroke (AIS). Among those, SAH seems to be of greater risk value [ 54 , 59 , 60 , 61 , 62 , 63 , 64 ]. It seems that the degree of neurological injury may be related to the severity of cardiac dysfunction.…”
Section: Heartmentioning
confidence: 99%